Role Perception and Performance of Women Members in Panchayat Raj - D.D. Suradkar,; S.D. Wangikar,; P.K. Wakale, (Journal of Agricultural Extension Management, 2025)
Panchayat Raj movement in India got initiated with Mahatma Gandhi's concept of Gram Swaraj, considering every village as a republic enjoying powers to decide at the bottom. Further the states were made responsible to organize village Panchayats and endow them with powers and authority to enable them to perform as self government.